Design of static var compensators using a general reactive energy definition - Liberado, Eduardo Verri; Souza, Wesley Angelino de; Pomílio, José Antenor; Paredes, Helmo Kelis Morales [UNESP]; Marafão, Fernando Pinhabel [UNESP] (My University, 2013)
This paper describes a methodology to design Static var Compensators (SVC) using the reactive energy definition from the Conservative Power Theory. The application of this methodology is presented through simulations of local and distributed compensation scenarios. Results show effective compensation of reactive current and load unbalance. Moreover, the harmonic distortion caused by thyristor controlled reactor has been suitable attenuated by passive filters designed in combination with the SVC.

Opisano metodologię projektowania kompensatora mocy biernej SVC wykorzystującą definicję energii biernej z Teorii Konserwacji Mocy. Symulacje wykazały że układ kompensuje prąd bierny i nierówność obciążenia. Tłumione są także harmoniczne.
Projektowanie kompensatora mocy biernej na podstawie definicji energii biernej
Keywords: Arc furnace; Conservative power theory; Reactive compensation; Static var compensator; Unbalance compensation; Kompensator mocy biernej; Teoria konserwacji mocy